Saccharomyces cerevisiae RAD5-encoded DNA repair protein contains DNA helicase and zinc-binding sequence motifs and affects the stability of simple repetitive sequences in the genome. - Johnson, R E (1992)
rad5 (rev2) mutants of Saccharomyces cerevisiae are sensitive to UV light and other DNA-damaging agents, and RAD5 is in the RAD6 epistasis group of DNA repair genes. To unambiguously define the function of RAD5, we have cloned the RAD5 gene, determined the effects of the rad5 deletion mutation on DNA repair, DNA damage-induced mutagenesis, and other cellular processes, and analyzed the sequence of RAD5-encoded protein. Our genetic studies indicate that RAD5 functions primarily with RAD18 in error-free postreplication repair. We also show that RAD5 affects the rate of instability of poly(GT) repeat sequences. Genomic poly(GT) sequences normally change length at a rate of about 10(-4); this rate is approximately 10-fold lower in the rad5 deletion mutant than in the corresponding isogenic wild-type strain. RAD5 encodes a protein of 1,169 amino acids of M(r) 134,000, and it contains several interesting sequence motifs. All seven conserved domains found associated with DNA helicases are present in RAD5. RAD5 also contains a cysteine-rich sequence motif that resembles the corresponding sequences found in 11 other proteins, including those encoded by the DNA repair gene RAD18 and the RAG1 gene required for immunoglobin gene arrangement. A leucine zipper motif preceded by a basic region is also present in RAD5. The cysteine-rich region may coordinate the binding of zinc; this region and the basic segment might constitute distinct DNA-binding domains in RAD5. Possible roles of RAD5 putative ATPase/DNA helicase activity in DNA repair and in the maintenance of wild-type rates of instability of simple repetitive sequences are discussed.